Safety Considerations When Dry Needling the Multifidi in the Thoracolumbar Region: A Cadaveric Study - Christi L. Williams; Christian R. Falyar; Ryan C. McConnell; Stacey Lindsley (International Journal of Sports Physical Therapy)
# Background